2020
DOI: 10.1177/0886109920978565
|View full text |Cite
|
Sign up to set email alerts
|

Using Anticarceral Feminism to Illustrate the Impact of Criminalization on the Lives of Individuals in the Sex Trades

Abstract: This research study is informed by anticarceral feminism to understand and highlight the experiences of violence and oppression that individuals in the sex trade experience as a result of police stings, raids, and incarceration. We present findings from 23 in-depth, qualitative interviews with men, women, and trans individuals who were arrested in the Los Angeles sex trade. More specifically, we explore experiences of violence that occurred interpersonally, systemically, and institutionally. Such experiences e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…An anti-carceral social work practice that works to defund the police, decriminalize poverty, and end the surveillance of community members is necessary to set the foundation for placing the interests of marginalized communities at the center of our practice (Desyllas et al, 2021). Despite the profession's shortcomings, this study views a potential for the profession to transform by separating itself from the source of its tension: its loyalty to the state.…”
Section: Discussionmentioning
confidence: 99%
“…An anti-carceral social work practice that works to defund the police, decriminalize poverty, and end the surveillance of community members is necessary to set the foundation for placing the interests of marginalized communities at the center of our practice (Desyllas et al, 2021). Despite the profession's shortcomings, this study views a potential for the profession to transform by separating itself from the source of its tension: its loyalty to the state.…”
Section: Discussionmentioning
confidence: 99%
“…Social workers use this information to develop a treatment plan. These plans tend to reflect “paternalistic ideas of what would be best for the participant's own good” (Capous-Desyllas et al, 2021, p. 526). Social workers often fail to inform participants of the purpose of these documents, and women who question this process may be perceived as ill-equipped for programming (Dewey & St. Germain, 2016).…”
Section: Sex Work Interventions Across Timementioning
confidence: 99%
“…These acts of kindness, along with service connection to benefits and other resources, are far outweighed by the power and control that police and providers have over participants' lives (Dewey & St. Germain, 2016). Capous-Desyllas et al (2021) found that criminalized sex workers often lost employment or custody of their children, lost affordable housing, or were unable to attend school. With these shortcomings in mind, it is troubling that fear of consequences such as jail sentences motivate participants to remain engaged with PDPs even when their needs are not being met (Wahab & Panichelli, 2013).…”
Section: Present Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We join in the growing voices of those who do not and will not accept a turn to policing as the answer to violence. The policing of sex work (Capous-Desyllas et al, 2020;Shih, 2021) has only added to vulnerability, detention and deportations, incarceration, and victimization not only by the police but by social work's paternalism and collusion with law enforcement. As Chicago social worker, Anjanette Young, reminds us in our recent editorial (Young et al, 2021), police violence against Black women is an everyday occurrence.…”
mentioning
confidence: 99%